The Role of Financial Literacy, Behavior, and Technology in Enhancing Business Sustainability Among Women-Owned MSMEsin Pekanbaru City - Siti A-Isah; Umi Rachmah Damayanti (Yayasan Almanar Pujud, 2025)
Business sustainability refers to a firm's ability to maintain operations and survive over the long term. This study investigates the influence of financial literacy, financial behavior, and financial technology on business sustainability among female MSME entrepreneurs in Pekanbaru City. Using a sample of 77 respondents, data were analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The results reveal that financial literacy and financial technology have a positive and significant effect on business sustainability, whereas financial behavior shows no significant effect. Overall, the three variables explain 42.2% of the variance in business sustainability, while the remaining 57.8% is attributed to other factors not examined in this study. These findings highlight the importance of enhancing financial literacy and technology adoption to strengthen the sustainability of female-led MSMEs.